"It feels as if she might return one day": A sense of unrealness as a predictor of bereavement-related emotional distress / "Tengo la sensación de que ella puede volver algún día": la sensación de irrealidad como un predictor del sufrimiento emocional relacionado con la pérdida. Issue 3 (2nd September 2017) - Boelen, Paul A.
Abstract: Impaired integration of the loss within autobiographical memory has been proposed as a critical factor in emotional distress following loss. Impaired integration is mainly an implicit process, but has an explicit counterpart, in the form of 'a sense of unrealness'. Unrealness can be defined as a subjective sense of uncertainty or ambivalence about the irreversibility of the separation. The current study used data from 199 individuals, bereaved in the previous year, to examine the cross-sectional and longitudinal linkage of unrealness with symptom levels of prolonged grief disorder (PGD), posttraumatic stress disorder (PTSD), and depression. Confirmatory factor analysis showed that manifestations of unrealness were distinguishable from (rather than overlapping with) symptoms of PGD. Regression analyses with the cross-sectional data showed that unrealness was concurrently associated with all three symptom outcomes. Regression analyses using the longitudinal data indicated that unrealness tapped at baseline predicted PGD-severity and depression-severity one year later, above and beyond baseline symptom levels and sociodemographic and loss-related variables.